2008
DOI: 10.1007/s10654-008-9236-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency electromagnetic fields; male infertility and sex ratio of offspring

Abstract: Concern is growing about exposure to electromagnetic fields and male reproductive health. The authors performed a cross-sectional study among military men employed in the Royal Norwegian Navy, including information about work close to equipment emitting radiofrequency electromagnetic fields, one-year infertility, children and sex of the offspring. Among 10,497 respondents, 22% had worked close to high-frequency aerials to a "high" or "very high" degree. Infertility increased significantly along with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 34 publications
1
43
0
1
Order By: Relevance
“…As for data on humans, several reports point to unfavourable effects of RF exposure on male fertility (18,19), while others contradict them (20). One study on humans (21) suggested that the duration of phone possession and daily transmission time correlated negatively with the proportion of rapid progressive motile sperm and positively with the proportion of slow progressive motile sperm.…”
Section: Discussionmentioning
confidence: 99%
“…As for data on humans, several reports point to unfavourable effects of RF exposure on male fertility (18,19), while others contradict them (20). One study on humans (21) suggested that the duration of phone possession and daily transmission time correlated negatively with the proportion of rapid progressive motile sperm and positively with the proportion of slow progressive motile sperm.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong clinical evidence that men diagnosed with infertility have significantly higher levels of ROS (Pasqualotto et al 2000). Some of the reports have suggested a possible linkage between mobile phone usage and male infertility (Baste et al 2008). Decreased sperm count and capacity of quails were reported by McRee et al (1983) as a result of MW exposure.…”
Section: Discussionmentioning
confidence: 99%
“…2 Many studies have examined the relationship of cell phone use and its effect on semen parameters and concluded that mobile phone use may cause a decrease in fertility. [3][4][5][6] To investigate the effects of cell phone radiation on semen parameters in human requires an in vivo exposure study which is not feasible, owing to ethical issues. Various in vitro studies using animal models have consistently demonstrated oxidative stress in different tissues (kidney, endometrium, eye, testis, brain, myocardial tissue and so on) in response to cell phone radiation.…”
Section: Introductionmentioning
confidence: 99%